SYSTEM TOOLS RENTAL PARTY ON RH. ROHMAN - Masuri Masuri; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2001)
With the rapid economic growth, the effect on the various activities of life, and thicauses people to want things to run fast-paced and practical.RH. Rohman is a place of party equipment rentals, rental leasing procedure is run bcoming directlyto place them. During this method of party equipment rentals are noyet using computerized, manual processing is to find the constraints among other datstorage is less neat and data search is not efficient because it takes a long time.Because of the complexity in such a lease transaction party tools, mechanics neededÂ system that can manage data effectively and efficiently rentals. So that the datobtained by the consumer or the tenant is always accurate and errors that can harmboth parties could belessened or removed.With the rental of data processing systems simple and efficient to make thtransaction process is rapid and uncomplicated. Accurate data processing make thleaders can analyze and then take the best step.